Genetic profile of syndromic retinitis pigmentosa in Portugal - Cortinhal, Telmo (2024)
Funding Information: Open access funding provided by FCT|FCCN (b-on). Part of this research was supported by EJPRD19-234 (Solve-RET) (to CR) regarding patients from Instituto Gama Pinto (IOGP). No other funding was received. Publisher Copyright: © 2024, The Author(s).